Implementasi Keperawatan Teknik Relaksasi Otot Progresif Pada Pasien Post Sectio Caesarea Dengan Nyeri Akut - Jaya, Herawati; Ningsih, Ratna; Syokumawena, Syokumawena (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: Labour caesarean section is a method of surgical delivery by making incisions in the abdominal wall and uterine wall. Post caesarean section injury to the operating area occurs which can cause tissue damage and pain. Progressive muscle relaxation technique is a relaxation therapy by tightening and relaxing the muscles at a time to give a feeling of relaxation. The purpose of this study was to reduce pain in postoperative patients caesarean section. Methods: The research design uses a descriptive method in the form of a case study. The subjects studied were 2 patients with the same cases and nursing problems, namely post-patients caesarean section with acute pain at Muhammadiyah Palembang Hospital. This research was conducted on 17-19 March 2023 and 20-22 March 2023 Results: Progressive muscle relaxation techniques have been shown to reduce acute pain in postoperative patients caesarean section. Before performing the progressive muscle relaxation technique both patients experienced moderate pain, after the progressive muscle relaxation technique was implemented the pain scale experienced by both patients became mild pain/ Conclusion: Implementation of progressive muscle relaxation techniques in postoperative patients caesarean section with acute pain can effectively reduce acute pain that is felt and can be applied to both patients.